Genetic diversity analysis of mango cultivars using inter simple sequence repeat markers - Pandit, Sagar S.; Mitra, Sirsha Sribas; Giri, Ashok P.; Pujari, Keshav H.; Patil, Bhimarao P.; Jambhale, Narayan D.; Gupta, Vidya S. (Current Science, 2007)
With 33 polymorphic Inter Simple Sequence Repeat (ISSR) markers, genetic diversity among 70 mango cultivars and a distant outgroup was analysed. Clustering was done using Dice and Jaccard coefficients with bootstrapping. Multivariate analysis was conducted using the Euclidean distances. Among the total 420 bands, 408 were polymorphic. Probability that any ISSR fragment is shared by two different cultivars was calculated to be 2.54 x 10(-1). Non-Indian mango cultivars were found genetically diverged from Indian mango germ pool. No separation was observed between North Indian and South Indian cultivars. Twelve different cultivar-specific bands were detected for six cultivars, which approved the effectiveness of ISSR markers in mango genetic diversity analysis.
Keywords: DNA finger printing; inter simple sequence repeat; Mangifera indica; principle coordinate analysis